Analyzing Analyzing Cost of Poor Quality and the Effectiveness of the Welder Performance Qualification Test in Mitigating Cost Inefficiency Risks in Steel Fabrication EPC Projects - Mohammad Fuad Zamroni; Nurhidayah; Abdullah Syakur Novianto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the effect of Welder Performance Qualification Test (WPQT) implementation on project cost performance through welder competency and repair rate within the Cost of Poor Quality (CoPQ) framework in the steel fabrication EPC industry. A quantitative explanatory approach was employed using data from WPQT records, Ultrasonic Testing (UT) reports, and welder competency questionnaires. The sample consisted of 52 welders involved in the the case project, selected through a census sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that WPQT positively influences welder competency, while welder competency significantly reduces repair rates. In turn, higher repair rates negatively affect project cost performance by increasing failure costs. Furthermore, welder competency and repair rate mediate the relationship between WPQT and project cost performance. These findings demonstrate that WPQT serves not only as a qualification requirement but also as a strategic quality control mechanism for improving cost performance in EPC projects